Faktor faktor yang berhubungan dengan kejadian hipotensi pada pasien dengan pasca spinal anestesi - Sunarsih Sunarsih; Yuspita Dewi Utari (JOURNAL OF Tropical Medicine Issues, 2026)
Background: Post-spinal anesthesia hypotension is a common complication that has a serious impact on patients' hemodynamic stability. At RSUD Jenderal Ahmad Yani Metro, the incidence of hypotension is reported to reach 20–25% of all patients undergoing spinal anesthesia procedures. This condition may worsen the prognosis, especially in patients with certain risk factors such as abnormal body mass index, poor hydration status, or intraoperative bleeding. Purpose: To determine the factors related to the incidence of hypotension in patients after spinal anesthesia in the operating room. Method: A quantitative method with a cross sectional design. The research sample was 50 patients who underwent spinal anesthesia and were taken using purposive sampling techniques. The variables studied were age, BMI, preloading fluid, vasopressor administration, amount of bleeding, and height of blockade. Data analysis was carried out univariate and bivariate using the chi-square. Results: The results showed that there was a significant relationship between BMI (p=0.004), preloading fluid (p=0.002), administration of vasopressor (p=0.006), and amount of bleeding (p=0.021). Meanwhile, the age factor (p=0.378) and the height of the anesthesia blockade (p=0.776) did not show a significant relationship. Conclusion: There is a relationship between BMI, preloading fluid, vasopressor administration and the amount of bleeding with the incidence of hypotension in patients with spinal anesthesia. Keywords: BMI; Hemodynamic Status; Hypotension; Preloading; Spinal Anesthesia.   Pendahuluan: Hipotensi pasca spinal anestesi merupakan komplikasi yang sering terjadi dan berdampak serius terhadap kestabilan hemodinamik pasien. Di RSUD Jenderal Ahmad Yani Metro, insiden hipotensi dilaporkan mencapai 20–25% dari total pasien yang menjalani tindakan spinal anestesi. Kondisi ini dapat memperburuk prognosis, terutama pada pasien dengan faktor risiko tertentu seperti indeks massa tubuh tidak ideal, status hidrasi buruk, atau perdarahan intraoperatif. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian hipotensi pada pasien pasca spinal anestesi di ruang bedah. Metode: Metode kuantitatif dengan desain cross sectional. Sampel penelitian sebanyak 50 pasien yang menjalani spinal anestesi dan diambil menggunakan teknik purposive sampling. Variabel yang diteliti adalah usia, IMT, cairan preloading, pemberian vasopressor, jumlah perdarahan, dan ketinggian blokade. Analisis data dilakukan secara univariat dan bivariat menggunakan uji chi-square. Hasil: Menunjukkan bahwa terdapat hubungan yang signifikan antara IMT (p=0.004), cairan preloading (p=0.002), pemberian vasopressor (p=0.006), jumlah perdarahan (p=0.021). Sedangkan faktor usia (p=0.378) dan ketinggian blokade anestesi (p=0.776) tidak menunjukkan hubungan yang signifikan. Simpulan: Terdapat hubungan antara faktor IMT, pemberian cairan preloading, pemberian vasopressor dan jumlah perdarahan dengan kejadian hipotensi pada pasien dengan spinal anestesi. Kata Kunci: Hipotensi; IMT; Preloading; Spinal Anestesi; Status Hemodinamik.